RESPON APLIKASI PGPR DAN KOMPOS Azolla microphylla TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) Var. Bima Brebes PADA MEDIA PASIR - Mubarok, Muhammad Fathan; Historiawati, Historiawati; Oktasari, Wike (JURNAL VIGOR, 2022)
ABSTRACTThe cultivation of shallots (Allium ascalonicum L.) on sand media as an effort to expand the land is needed to increase the production of shallots. Characteristics of sand media is low nutrient, so it is necessary to add organic matter to increase nutrient on sand media. This study aims to examine the response of the application of PGPR and Azolla.microphylla compost to the growth and yield of shallots on sand media. The research was conducted from January to March 2022 at KP3 Bandongan, Bandongan, Magelang with an altitude of 400 m above sea level. The research method was arranged in a factorial manner in a Randomized Complete Block Design (RCBD) with consisted of two factors and three blocks as replicates. Data were analyzed using analysis of variance (Anova) if they were significantly different, an orthogonal polynomial test was performed. The results showed that the PGPR concentration of 17,04 ml/l gave the best average number of tubers per clump compared to other treatments. The dose of A. microphylla compost and the interaction of the two treatments significantly affected the number of tubers per clump but did not significantly differ on other parameters. The low nutrient content of A. microphylla compost and high rainfall during the study caused the treatment applied to not be able to provide optimal results on the growth and yield of shallot plants. Keywords: compost A.microphylla, sand media, shallots, PGPR